CHEST PAIN AND SINGLE TROPONIN - Süha Serin; Bahadir Çağlar (Journal of Contemporary Medicine, 2020)
Aim: It is important to exclude the diagnosis of acute coronary syndrome quickly and accurately. This study aims to exclude the diagnosis of acute myocardial infarction (AMI) with a single troponin value in patients with appropriate clinical evaluation and electrocardiography (ECG) Materials and Methods: Among the patients who were followed up with a pre-diagnosis of AMI and for whom a HEART score was calculated, patients whose high sensitive troponin I result was found below the limit of detection (LoD) value and who were discharged is included in study. All patients were contacted on the 30th day of discharge. The status of "major adverse cardiac events" (MACE-30) in the last 30 days was questioned. Results: The HEART score of 122 patients (73.1%) in the study was found to be at low risk while 45 (26.9%) as moderate. MACE-30 developed in only 5 patients (3%). Of the 5 patients who developed Mace; The HEART score of 3 (60%) was determined as 5, whereas the heart score of 2 (40%) was 6. p